2023
DOI: 10.1001/jamanetworkopen.2022.54928
|View full text |Cite
|
Sign up to set email alerts
|

US Medical School Admissions Leaders’ Experiences With Barriers to and Advancements in Diversity, Equity, and Inclusion

Abstract: ImportanceDespite decades-long calls for increasing racial and ethnic diversity, the medical profession continues to exclude members of Black or African American, Hispanic or Latinx, and Indigenous groups.ObjectiveTo describe US medical school admissions leaders’ experiences with barriers to and advances in diversity, equity, and inclusion.Design, Setting, and ParticipantsThis qualitative study involved key-informant interviews of 39 deans and directors of admission from 37 US allopathic medical schools across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 51 publications
0
20
0
Order By: Relevance
“…The siloed nature of many diversity initiatives can lead to a decentralization that stymies meaningful progress and can render diversity practitioners frustrated, isolated, and burnt out . We agree with Ko and colleagues call for greater coordination in order to make meaningful positive changes in diversity, but additional resources are a prerequisite. The study found that overemphasis on the MCAT and other numerical metrics was partially due to convenience given the large volume of applications received.…”
mentioning
confidence: 54%
See 4 more Smart Citations
“…The siloed nature of many diversity initiatives can lead to a decentralization that stymies meaningful progress and can render diversity practitioners frustrated, isolated, and burnt out . We agree with Ko and colleagues call for greater coordination in order to make meaningful positive changes in diversity, but additional resources are a prerequisite. The study found that overemphasis on the MCAT and other numerical metrics was partially due to convenience given the large volume of applications received.…”
mentioning
confidence: 54%
“…We believe that the study by Ko et al is a call to action for medical school leaders, gatekeepers, and educators who have a unique opportunity to address many of the persistent challenges in advancing diversity within medical schools. Although this qualitative study of a diverse sample of deans and directors of admissions across 37 allopathic schools in the United States was not nationally representative, it nonetheless makes a major contribution to the literature by unmasking processes where racism can operate in medical school admissions.…”
mentioning
confidence: 99%
See 3 more Smart Citations